The effect of wound dressings on the pH stability of fluids - UZUN, MUHAMMET (MA HEALTHCARE LTD, 2012)
Objective: To investigate and evaluate the effect of 20 commercial wound dressings on the pH values of selected fluids upon contact, over a period of 7 days. Method: The effect of the dressings on the pH of two different solutions, solution A (2.298g sodium chloride [NaCl], 0.368g calcium chloride [CaCl2] dihydrate added to I litre of de-ionised water) and distilled water, was investigated over a period of 7 days. Two different methods for contacting fluid with the dressings were used, to simulate wounds with different levels of exudate: i) immersing the dressing in 35ml fluid, and ii) adding 5ml drop-wise onto the dressing's absorbent pad on a daily basis. Results: On immersion of the dressings, the pH values of the fluids changed quite appreciably over time, with similar results for both methods. The lowest pH values were found with the hydrocolloid dressings, for both solution A and distilled water. The foam dressings had an alkaline effect on the fluids; in most cases, they increased the fluid's pH significantly. The non-woven dressings reduced the pH of both fluids to a lesser extent than the hydrocolloid dressings. The hydroactive dressings decreased the pH value of solution A and increased the pH of distilled water. Conclusion: This study demonstrates that the pH values of the fluids are not constant, likely due to the complicated nature of the dressings' chemical structures and designs. Thus, optimisation of pH level to meet the requirements of any specific wound types and healing processes must consider the complex nature of the dressing. The increase in pH value of the wound over time needs to be minimised in order to maximise the effectiveness of the healing therapy.
Keywords: pH; in vitro; wound healing; wound dressing; IN-VITRO